Microbial decontamination of peeled chestnuts by electrolyzed water and its effect on biochemical and sensory properties - Kim, Juhwa; Pradeep Puligundla,; Mok, Chulkyoon (Penerbit Universiti Kebangsaan Malaysia, 2019)
The aim of this study was to improve the hygienic quality of peeled chestnuts by electrolyzed water (EW) treatment. Additionally, the effect of the treatment on biochemical and organoleptic properties of chestnuts was assessed. The counts of mesophilic aerobic bacteria (MAB) and yeasts and mold in peeled chestnuts were found to be 8.01 and 7.96 log CFU/g, respectively. Electrolyzed water was produced at four different combinations of brine and deionized water (A, B, C and D; with chlorine levels of 230, 470, 250 and 490 mg/L, respectively). Following treatment for 10 min using EW generated at the combination B (EW-B), the counts of MAB and yeasts and mold in peeled chestnuts were reduced by 1.61 and 1.65 log CFU/g, respectively, compared with distilled water treatment. Although EW-D possessed relatively high chlorine levels, its inactivation effect was found to be reduced after 5 min of treatment. Soluble solids and total phenolic content (TPC) of peeled chestnuts were decreased significantly (p < 0.05) with increasing EW treatment time. However, 2, 2-diphenyl-1-picrylhydrazyl free radical scavenging activity and sensory qualities were insignificantly altered by EW treatment. In conclusion, EW, especially EW-B, can potentially be used to reduce microbial load in peeled chestnuts with no or only minor negative effects on their biochemical and sensory qualities.